First Insights Into Bacterial Gastrointestinal Tract Communities of the Eurasian Beaver (Castor fiber) - Pratama, Rahadian; Schneider, Dominik; Böer, Tim; Daniel, Rolf (Frontiers in Microbiology, 2019)
The Eurasian or European beaver (Castor fiber) is the second-largest living rodent after the capybara. It is a semi-aquatic animal known for building dams and lodges. They strictly feed on lignocellulose-rich plants and correspondingly harbor cellulolytic microbial communities in their digestive tract. In this study, the bacterial community composition, diversity and functional profile of different gut compartments ranging from stomach to colon have been explored. A total of 277 bacterial operational taxonomic units (OTUs) at species level were obtained from the gut systems of two males (juvenile and subadult) and one subadult female beaver. In general, cecum and colon are dominated by Firmicutes and Actinobacteria. High abundance of Bacteroidetes was observed only in male juvenile beaver cecum and colon, suggesting that the bacterial composition changes with age. Within the cecum and colon, members of known cellulase-producing bacterial taxa including the families Ruminococcaceae, Lachnospiraceae, and Clostridiaceae 1 were detected. The presence of putative genes encoding cellulolytic and carbohydrate-degrading enzymes indicated also the degradation of recalcitrant plant material in both gut compartments. The bacterial community in the gut systems of the Eurasian beaver differed from that of the North American beaver. Higher abundance of Actinobacteria and lower abundances of Bacteroidetes were recorded in the Eurasian beaver. Similar differences were obtained to bacterial communities of termites and herbivorous animals such as bovine. The data presented in this study provides the first insight into bacterial communities in the gut system of the Eurasian beaver.